The Manifestation of Indonesian Democracy; Between Pancasila State of Law and Islamic Nomocracy - Sarip Sarip (Jurnal Hukum Novelty, 2018)
The state of Pancasila law is a tool for people who have the power to regulate human relations in society and regulate the symptoms of power in society. As a country with the largest Muslim population in the world, Indonesia does not make Islam its legal basis. The Islamic Nomocracy and its values are embedded in the state of Pancasila law, as well as manifestation of democracy itself. Through these hyphoteses, the writer tries to find a common flateform between Pancasila and the Islamic Nomocracy in the formation of Indonesian democracy. This classic problem requires special attention, because the debate always triggers reactions and actions. Islam as a religion with complex system of living is believed to be a powerful mechanism in dealing with various life problems encountered. The Shari’ah consists of a combination of pre-Islamic customs and habits with principles and laws originated from the Qur’an and authentic prophetic tradition. Islamic scholars try to form Islamic teachings as ethical and national policies. Even so, the principle of the Pancasila state was accepted as final, at least there were Islamic nomocracy values embedded in the Pancasila while at the same time they contributed to build Indonesia’s democracy as a modern country. The theological values in the Pancasila and islamic nomocracy should not be a mere formal rule, but should address the substance of democracy in Indonesia. The rule of law must be supported by a democratic system because there is a clear correlation between the rule of law which relies on the constitution, and the sovereignty of the people which is carried out through a democratic system. In a democratic system, people’s participation is the essence of this system. However, democracy without legal regulation will lose form and direction, while law without democracy will lose meaning.